Women’s Role and Position During Democratic Transition Period: A Comparison of Indonesia and Thailand - Kurniawati Hastuti Dewi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2022)
This paper observes the historical, cultural, political, and social aspects of Indonesian and Thailand women to understand the progress of the women’s role and position in the two countries, especially during the democratic transition period. This is qualitative research that utilized library sources to collect information and data through various resources such as books, documents, historical books, and webistes dated back from 1970s to 2000s in Indonesia and Thailand. Although there are similarities in development programs to address women's role and position before democratization in Indonesia and Thailand as both of them mainly focused on “practical gender interests”. Interestingly, this paper reveals that during the democratic transition period, Indonesian women’s role and position in politics are one step ahead. This is due to the political stability, persistent commitment of the government to the gender equality agenda, and growing support from progressive Muslim leaders. In contrast, political turbulence due to often military coups which result in the government’s slow performance for women’s advancement combined with less support from Buddhist leaders slowed the progress of Thailand women. This paper highlights the important role of the government policy on gender equality for women’s advancement, political stability, and the role of the majority religion (Islam in Indonesia and Theravada Buddhism in Thailand) to support women's role and position in politics.Tulisan ini mengkaji aspek sejarah, budaya, politik, dan sosial perempuan Indonesia dan Thailand untuk memahami perkembangan peran dan posisi perempuan di kedua negara, terutama pada masa transisi demokrasi. Ini adalah penelitian kualitatif yang memanfaatkan sumber perpustakaan untuk mengumpulkan informasi dan data melalui berbagai sumber seperti buku, dokumen, buku sejarah, dan situs web dari tahun 1970-an hingga 2000-an di Indonesia dan Thailand. Meskipun ada kesamaan dalam program pembangunan untuk mengatasi peran dan posisi perempuan sebelum demokratisasi di Indonesia dan Thailand karena keduanya berfokus pada “kepentingan gender praktis”. Menariknya, tulisan ini mengungkapkan bahwa selama masa transisi demokrasi peran dan posisi perempuan Indonesia dalam politik selangkah lebih maju. Hal ini disebabkan oleh stabilitas politik, komitmen pemerintah yang gigih terhadap agenda kesetaraan gender dan dukungan yang semakin besar dari para pemimpin Muslim progresif. Sebaliknya, gejolak politik akibat seringnya kudeta militer yang mengakibatkan lambatnya kinerja pemerintah untuk kemajuan perempuan ditambah dengan kurangnya dukungan para pemimpin Buddhis memperlambat kemajuan perempuan Thailand. Tulisan ini menyoroti pentingnya peran kebijakan pemerintah tentang kesetaraan gender untuk kemajuan perempuan, stabilitas politik, dan peran agama mayoritas (Islam di Indonesia dan Buddhisme Theravada di Thailand) untuk mendukung peran dan posisi perempuan dalam politik.